Functional analysis of newly described 45S SSU* complex in Trypanosoma brucei - Ridlon, Lucie (Jihočeská univerzita, 2014)
This thesis addresses several hypothetical roles of a newly described and very unusual 45S SSU* complex in procyclics Trypanosoma brucei. RNAi interference of several 45S SSU* subunits revealed essentiality of this complex for its mitochondrial translation machinery. The effect of ablation of selected subunits on mitochondrial-encoded mRNAs is complex and not fully understood.
Functional analysis of newly described 45S SSU* complex in Trypanosoma brucei